2006
DOI: 10.1021/ja065552h
|View full text |Cite
|
Sign up to set email alerts
|

15N−15N J-Coupling Across HgII:  Direct Observation of HgII-Mediated T−T Base Pairs in a DNA Duplex

Abstract: N−N J-coupling across a metal center (2 J NN) was clearly detected in a biological macromolecule (DNA duplex) for the first time. By using 2 J NN, the base pairing mode of mercury-mediated T−T pairs (T−HgII−T) was definitely determined. This pairing mode was found to be a novel metal ion-binding mode for DNA and RNA molecules, in which imino proton−metal exchange processes are included. Accordingly, 2 J NN is highly important for the determination of the chemical structures of metal-mediated base pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
364
3
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 533 publications
(383 citation statements)
references
References 24 publications
12
364
3
4
Order By: Relevance
“…This DNA is rich in thymine and Hg 2+ can be selectively chelated by thymines to fold the DNA into a hairpin (23).…”
Section: Introductionmentioning
confidence: 99%
“…This DNA is rich in thymine and Hg 2+ can be selectively chelated by thymines to fold the DNA into a hairpin (23).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of 15 N labeled thymine nucleobases allowed the first direct spectroscopic proof of such T-Hg 2+ -T base pairs: 15 N NMR studies revealed a 15 N-15 N J-coupling across the Hg 2+ ion (see Section 5). [51] A highly selective oligodeoxyribonucleotide Hg 2+ sensor could be created based on this specific interaction. [52,53] Recent studies showed that also an RNA duplex synthesized by in vitro transcription can incorporate Hg 2+ ions to form uracil-Hg 2+ -uracil base pairs.…”
Section: Artificial Metal Ions-nucleic Acids Systemsmentioning
confidence: 99%
“…The stability of this Hg 2+ mediated base pair is comparable to a normal Watson-Crick base pair. [51] using different probes and mimics. These methods range from the observation of chemical shift changes, which can be done with basically any metal ion, over paramagnetic line broadening studies, to the most direct way of the detection of NOE contacts between the nucleic acid and probes like cobalt(iii)hexammine or the ammonium ion.…”
Section: Artificial Metal Ions-nucleic Acids Systemsmentioning
confidence: 99%
See 2 more Smart Citations